2012
DOI: 10.5861/ijrsll.2012.164
|View full text |Cite
|
Sign up to set email alerts
|

Writers’ self-representation in academic writing: The case of computer engineering research articles by English versus Iranian writers

Abstract: It is widely acknowledged that academic writing is not just about communicating an ideational content; it is also about the representation of self. The purpose of this study was to investigate the tendency of Iranian and American writers for self-representation which is realized by means of writers' explicit (first person self-references) and implicit self (imperative forms and attitude markers) in computer engineering research articles. In this study, 40 published research articles written in English by Irani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This leads us to a question that is of interest for the present study, namely whether writers transfer knowledge of academic writing from their first language to their second language. Kuhi, Tofigh, and Babaie (2013) investigated 40 research articles within computer engineering, written in English by 20 Iranian and 20 American researchers. The greatest difference was in the use of exclusive versus inclusive "we" in the articles.…”
mentioning
confidence: 99%
“…This leads us to a question that is of interest for the present study, namely whether writers transfer knowledge of academic writing from their first language to their second language. Kuhi, Tofigh, and Babaie (2013) investigated 40 research articles within computer engineering, written in English by 20 Iranian and 20 American researchers. The greatest difference was in the use of exclusive versus inclusive "we" in the articles.…”
mentioning
confidence: 99%
“…To date, numerous studies have found some variations in the use of linguistic realization of authorial identity between native and non-native English writers in cultural contexts such as follows: native English and Chinese writers (Lin, 2013), native English and Japanese writers (McCrostie, 2008), native English and Spanish writers (Pérez-Llantada, 2007), native English and Iranian writers (Kuhi, Tofigh, & Babaie, 2013), native English and French, Dutch, Swedish writers (Petch-Tyson, 1998). Among cross-cultural studies of authorial identity, the comparison between native English and Thai writers are found to be lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The ideological image may have unconsciously been integrated in the teaching and learning process in the Philippines, further legitimizing an identity of their group in the process. Kuhi, Tofigh, and Babaie (2013) claimed that writers project a personal identity in their writing. They continued that "writers cannot avoid projecting an impression of themselves and how they stand in relation to their arguments, their community and their readers" (p. 36).…”
Section: Introductionmentioning
confidence: 99%